Firm characteristics and country institutional development: business relationships with foreign firms in transition economies - Ferreira, Manuel Portugal (2009)
The composition of firms' foreign business networks has been attended to in recent research but has seldom been subjected to empirical study in transition economies. In this study, we test hypotheses related to the composition of firms' foreign business relationships. First, we suggest that firms' characteristics matter for building a network of ties the foreign agents. Then, we consider the moderating effect of the degree of institutional development of the home country to assess to extent to which firms' foreign business relationships in transition economies are affected by the institutional development. We conduct a set of logistic regressions and one OLS regression to investigate the composition of firms' business relationships using firm-level data from 24 transition economies. The results indicate that firm size and membership in trade associations are good predictors of foreign business relationships – specifically, relationships with foreign investors, customers, and suppliers - and also of the diversity of foreign relationships. The country's institutional development radically changes which firms' characteristics matter in forming business relationships.